Рекурсивная потоковая модель MPLS - Овчинников, К. А.; Руккас, К. М.; Горюнов, А. А. (ХНУРЭ, 2011)
The given work is devoted to the modeling of modern telecommunication systems. Flow modeling problems has been described. A new flow model for MPLS with losses and delays has been suggested.
Keywords: телекоммуникационные услуги; совместимость сетей